Improving Digital Literacy of Vocational School Students through the Utilization of Google Workspace - Khansha Sindra Irfani; Sri Widi Lestari; Wulan S; Mely W; Vadisya (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community engagement program is designed to enhance the digital literacy of students at State Vocational High School 50 Jakarta through structured training and guided mentorship centered on the effective utilization of Google Workspace. Method: Implementation followed a multi-stage framework comprising stakeholder orientation sessions, intensive skill-building workshops, practical integration of digital tools into classroom instruction, and periodic evaluative assessments. Practical Applications: The initiative strengthens students' readiness for participation in the digital workforce and aligns with the targets of Sustainable Development Goal 4 (Quality Education).  Conclusion: Observational data reveal a marked improvement in students' proficiency with Google Docs and Google Classroom, accompanied by positive shifts in educators' pedagogical practices, as evidenced by the growing integration of digital technologies into instructional methodologies.